2000
DOI: 10.1111/j.1365-2338.2000.tb00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for resistance to Didymella bryoniae in rootstocks of melon

Abstract: Glasshouse evaluations of rootstocks of melon for resistance to Didymella bryoniae were conducted on different cucurbits previously selected as resistant or partially resistant to race 1,2 of Fusarium oxysporum f. sp. melonis. Cucumis anguria, C. ficifolius, C. figarei, C. metuliferus, C. zeyheri and Benincasa hispida showed a very high degree of resistance to D. bryoniae both on leaves and stems. Among the commercial rootstocks, Cucurbita hybrids ELSI, ES 99‐13, RS 841, displayed a similar level of resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It has been shown that grafting exhibits excellent tolerance to serious soil-borne diseases. For instance, grafted watermelons show increased resistance to Fusarium L. and Verticillium N., bell peppers to Phytophthora B., and melons to Didymella bryoniae R., showing grafting’s role in tolerating diseases [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that grafting exhibits excellent tolerance to serious soil-borne diseases. For instance, grafted watermelons show increased resistance to Fusarium L. and Verticillium N., bell peppers to Phytophthora B., and melons to Didymella bryoniae R., showing grafting’s role in tolerating diseases [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%